PUISI BALI MODERN “SIWA RATRI” KARYA I KETUT RIDA: KAJIAN TRANSFORMASI TEKS (Modern Bali Poem “Siwa Ratri” By I Ketut Rida: Text Transformational Analysis) - Ni Nyoman Tanjung Turaeni (SAWERIGADING, 2009)
This research discusses about transformation of teks Kakawin Siwa Ratri Kalpa in to modern Bali poem naming “ Siwa Ratri” by I Ketut Rida. The theory used in this research is intertextual theory, semiotic theory, and hermeneutics. Particularly, this research’s aim is to find out the problem mentioned above and to preserve Bali literary work as unvaluable wealth that implies traditional variation. Theorical use of this research is to be on of knowledge source in literary field, especially Bali literary in attempting to development of literary sciences. Pratically, this research is useful to encourage good behavior and to produce creative appreciation material for the next generation and to become the guldnce for the people in choosing and functioning as facilitation of celebrating Hindu ceremony.